Modified sodium ion battery positive electrode material and preparation method thereof, sodium ion battery
Coating sodium ion battery positive electrode materials with Co5.4N and FeSe2 addresses the limitations of existing materials, enhancing conductivity and structural stability to improve the cycle life and capacity of sodium-ion batteries.
Patent Information
- Application Number
- CN202411330168.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Sodium-ion batteries face challenges with thermal stability, poor energy density, and limited cycle and rate performance due to the adverse effects of moisture and poor air stability of common positive electrode materials, which hinder their application in large-scale energy storage systems.
A modified sodium ion battery positive electrode material is developed by coating a sodium ion battery positive electrode material substrate with Co5.4N and FeSe2, enhancing conductivity and structural stability through a simple and effective modification process.
The coating improves the capacity and cycle life of sodium-ion batteries, achieving better electrochemical performance and stability under high temperature conditions.
Smart Images

Figure CN118867210B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular relates to a coating method for a sodium ion battery positive electrode material. Background Art
[0002] With the development of renewable energy and clean energy, there is a demand for large-scale energy storage. In order to smoothly access and fully absorb renewable energy generation, and to achieve optimal management and efficient use of energy, the coordinated application of centralized energy storage, distributed energy storage, and DC distribution networks is required. In principle, secondary batteries suitable for large-scale energy storage applications must be highly safe, environmentally friendly, low-cost, abundant in resources, and have excellent electrochemical properties such as long life and high power density. Resource-rich and environmentally friendly sodium-ion battery technology has become a hot topic in current research.
[0003] The research on sodium-ion batteries is affected by problems such as thermal stability and poor energy density. The cycle and rate performance of the battery are limited, and there is a lot of room for improvement. However, the common positive electrode materials are easily affected by moisture, have poor air stability, and are prone to adverse effects. The positive electrode material is one of the core parts of sodium-ion batteries, and plays a vital role in improving the battery's rate, specific capacity, operating voltage, and cycle stability. Sodium-ion batteries using existing sodium-ion battery positive electrode materials generally have poor cycle performance and cannot meet life requirements, especially under high temperature conditions. In recent years, people have mainly used morphology control, carbon coating, doping and other technologies to modify the positive electrode materials, but the cycle performance and life of sodium-ion batteries still need to be improved. The coating strategy is a simple and effective modification method. Summary of the invention
[0004] In response to the above technical problems, the present application provides a modified sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery.
[0005] To achieve the above objectives, this application proposes the following solutions:
[0006] In a first aspect, a modified sodium ion battery positive electrode material is provided, comprising a sodium ion battery positive electrode material substrate and a coating layer located on at least a portion of the surface of the substrate, wherein the coating layer material is Co 5.4 N and FeSe2.
[0007] In a second aspect, a method for preparing a positive electrode material for a sodium ion battery is provided, comprising:
[0008] The sodium ion battery positive electrode material matrix, Co 5.4 N and FeSe2 are mixed in anhydrous ethanol, and heated and stirred until the solvent is evaporated to dryness to obtain a solid mixture;
[0009] After the solid mixture is dried and sintered, a modified sodium ion battery positive electrode material is obtained.
[0010] In a third aspect, a sodium ion battery is provided, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0011] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0012] By coating Co on the surface of the positive electrode material of sodium ion battery 5 .47 N and FeSe2 can improve the capacity of the positive electrode material of sodium-ion batteries, catalyze the conversion of sodium ions, enhance conductivity, improve structural stability, thereby increasing the cycle life of the battery and achieving better capacity.
[0013] The coating modification method is simple and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 This is the EDS image of the calcined product in step (3) of Example 1.
[0016] Figure 2 The uncoated NaNi in Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 SEM images of O2 and coated modified sodium ion battery cathode materials, where (a) is uncoated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 (a) is the SEM image of O2, and (b) is the SEM image of the coated modified sodium ion battery positive electrode material.
[0017] Figure 3 The positive electrode materials finally obtained in Example 1 and Comparative Examples 1-5 and NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Cycling performance curve of the battery assembled with O2.
[0018] Figure 4 The positive electrode materials finally obtained in Example 2 and Example 3 and NaNi 0.5 Fe 0.3 Mn 0.2O2、NaNi 0.2 Fe 0.4 Mn 0.4 Cycling performance curve of the battery assembled with O2. DETAILED DESCRIPTION
[0019] The present invention provides a modified sodium ion battery positive electrode material, comprising a sodium ion battery positive electrode material substrate and a coating layer located on at least a portion of the surface of the substrate, wherein the coating layer material is Co 5.4 N and FeSe2.
[0020] Cobalt nitride has high electrical properties and chemical stability. 5.4 N has a certain catalytic effect and has a high potential in the field of energy storage. Selenide has a high theoretical capacity and is considered to be a promising negative electrode material. FeSe2 has the characteristics of high specific capacity, low toxicity and environmental friendliness, but the volume change is obvious. 5.4 Combining N with FeSe2 to modify the positive electrode material of the battery can overcome their respective defects, give full play to their advantages, and achieve unexpected results. 5.4 N combined with iron diselenide FeSe2 as a coating layer can improve the capacity to a certain extent, catalyze the conversion of sodium ions, enhance conductivity, and improve structural stability, thereby increasing the cycle life of the battery and achieving better capacity.
[0021] In some embodiments, the chemical formula of the sodium ion battery positive electrode material matrix is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4.
[0022] In some preferred embodiments, in the coating layer, Co 5.4 The mass ratio of N to FeSe2 is 1:4~4:1. The applicant has found through research that when Co 5.4 When the mass ratio of N to FeSe2 is 1:4~4:1, the modification effect is better. 5.4 Too much N or too much FeSe2 may result in poor cycle stability or low capacity, and it is impossible to ensure that the capacity is increased while enhancing the cycle stability.
[0023] In some preferred embodiments, the coating layer material accounts for 1-5% of the mass of the sodium ion battery positive electrode material matrix.
[0024] The present invention also provides a method for preparing a modified sodium ion battery positive electrode material, comprising:
[0025] The sodium ion battery positive electrode material matrix, Co 5.4N and FeSe2 are mixed in anhydrous ethanol, and heated and stirred until the solvent is evaporated to dryness to obtain a solid mixture;
[0026] After the solid mixture is dried and sintered, a modified sodium ion battery positive electrode material is obtained.
[0027] In some preferred embodiments, the sintering temperature is 300-450° C. and the sintering time is 2-4 hours.
[0028] Alcohol as an organic solvent can disperse the cobalt nitrate, which is beneficial to the subsequent nitridation; if dispersed in water, the cobalt nitrate will usually agglomerate, and the subsequent sintering may not be able to fully contact with other raw materials.
[0029] The purpose of stirring is to achieve the sodium ion battery positive electrode material matrix, Co 5.4 The mixing uniformity of N and FeSe2, the stirring speed can meet the conventional mixing requirements, the purpose of heating is to evaporate and remove the anhydrous ethanol in the solution system to obtain a mixed solid, and the heating temperature can ensure the evaporation of the anhydrous ethanol. In some preferred embodiments, the heating temperature of the heating and stirring is 50-120°C. In order to achieve uniform heating, intermittent heating can be selected, and the reaction system can be placed in an oil bath.
[0030] In some preferred embodiments, the sodium ion battery positive electrode material matrix, Co 5.4 The mixing of N and FeSe2 in anhydrous ethanol includes: dispersing the sodium ion battery cathode material matrix in anhydrous ethanol, and then adding Co 5.4 N and FeSe2 are mechanically mixed. The sodium ion battery positive electrode material matrix is first dispersed uniformly, and then Co 5.4 N and FeSe2 are added for further mechanical mixing, which is beneficial to improve the mixing uniformity of the materials and avoid poor mixing uniformity caused by agglomeration in the solution due to simultaneous addition of the materials. Further preferably, the dispersion can be ultrasonic or mechanical stirring dispersion, and the mechanical mixing can also be achieved by stirring or ultrasound.
[0031] In some preferred embodiments, the Co 5.4 The preparation method of N comprises: dissolving cobalt nitrate in ethanol to form a solution, heating and stirring the solution to evaporate to obtain a solid, drying the solid to obtain a precursor, calcining the precursor in an ammonia atmosphere to obtain Co 5.4 N.
[0032] The ammonia atmosphere can be achieved by continuously introducing ammonia. The flow rate of ammonia is regulated based on the principle of fully carrying out the nitridation reaction and not blowing away the reactants.
[0033] More preferably, the calcination temperature is 400-1000° C., more preferably 600-1000° C., and the calcination time is 1-5 hours. The calcination time can be adaptively adjusted according to the calcination temperature and the like.
[0034] In the actual calcination process, according to the performance of the calcination equipment, the calcination efficiency, and the uniformity of the material heating, the heating rate during calcination is preferably 3-8°C·min -1 After the calcination and heat preservation, according to the results of multiple experiments, the cooling rate after calcination is preferably 3-8 ℃·min -1 .
[0035] Co 5.4 In the preparation method of N, drying can be carried out by conventional drying methods, such as vacuum drying, oven drying or low-temperature freeze drying, etc. In order to reduce costs, low-temperature freeze drying is usually not used.
[0036] In some preferred embodiments, the preparation method of FeSe2 includes: preparing ferric nitrate solution A, dissolving selenium powder in hydrazine hydrate to obtain solution B, adding solution B dropwise to solution A, stirring, and performing a hydrothermal reaction, separating the product from the solid and liquid, washing and drying to obtain FeSe2.
[0037] More preferably, the molar ratio of the selenium powder to ferric nitrate is 1-3 mmol:1 mmol; and the ratio of the selenium powder to hydrazine hydrate is 1-3 mmol:5 mL.
[0038] More preferably, the temperature of the hydrothermal reaction is 120-220° C., and the time of the hydrothermal reaction is 8-15 h.
[0039] In the preparation method of FeSe2, conventional washing reagents can be used for washing in order to remove impurities. For example, deionized water and ethanol can be used for washing. Preferably, deionized water is used for washing first, and then ethanol is used for washing. In this way, drying can be achieved at room temperature. Centrifugal separation or other separation methods can be used for solid-liquid separation.
[0040] The present invention also provides a sodium ion battery, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0041] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0042] Embodiment 1:
[0043] Step (1): Mix 1 g Co(NO3)2·6H2O and 50 mL ethanol in a beaker equipped with a stirring bar and stir in air at room temperature for 24 h to form a homogeneous solution;
[0044] Step (2): evaporating the obtained homogeneous solution in an oil bath at 100° C. and vacuum drying overnight to obtain a precursor;
[0045] Step (3): The precursor was heated in an NH3 atmosphere (flow rate 100 mL min - 1 ) and calcined at 700 °C for 3 h, then cooled; the heating rate was 5 °C min -1 ; Cooling rate: 3.3 ℃·min -1 ; Get Co 5.4 N;
[0046] Figure 1 This is the EDS elemental analysis diagram of the calcined product in step (3). By analyzing the spectrum of the calcined product, the elemental composition and content in the calcined product can be determined, and the number of atoms can be detected, and the proportion of each atom can be calculated.
[0047] The contents of Co and N are shown in Table 1.
[0048] Table 1
[0049]
[0050] It can be determined that the atomic ratio of Co atoms to N atoms in the calcined product is about 5.4:1, that is, the product is Co 5.4 N.
[0051] Step (4): first, take 1 mmol of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water to obtain a ferric nitrate solution; then take 2 mmol of selenium powder and dissolve it in 5 mL of hydrazine hydrate to obtain a selenium-containing solution; add the selenium-containing solution dropwise to the ferric nitrate solution, and stir magnetically for 15 min to obtain a mixed solution;
[0052] Step (5): The mixed solution obtained in step (4) was transferred to a 100 mL hydrothermal reactor, maintained at 170° C. for 12 h, and then cooled to room temperature;
[0053] Step (6): The reaction product obtained in step (5) was washed by centrifugation with deionized water and ethanol for three times respectively, dried at room temperature, and black powder FeSe2 was collected;
[0054] Step (7): Prepare the positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 was ultrasonically dispersed in 100 mL of anhydrous ethanol, and then 2 wt% of Co as the positive electrode material was added. 5.4 N and 2wt% FeSe2 were mixed evenly;
[0055] Step (8): evaporate the ethanol from the slurry obtained in step (7) in an oil bath at 80°C, and then dry it thoroughly in an oven at 120°C;
[0056] Step (9): The dried material obtained in step (8) is sintered in a muffle furnace at a sintering temperature of 400°C for 3 h to obtain a coated modified sodium ion battery positive electrode material.
[0057] Figure 2 For uncoated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and the SEM images of the coated and modified sodium ion battery positive electrode material obtained in this embodiment. It can be found from the figure that the layered structure of the layered oxide surface before coating is more obvious, with more obvious edges and corners, while the surface of the positive electrode material after coating is slightly passivated. The above results can explain the existence of the coating layer.
[0058] Comparative Example 1:
[0059] Step (1): Mix 1 g Co(NO3)2·6H2O and 50 mL ethanol in a beaker equipped with a stirring bar and stir in air at room temperature for 24 h to form a homogeneous solution;
[0060] Step (2): evaporating the obtained homogeneous solution in an oil bath at 100° C. and vacuum drying overnight to obtain a precursor;
[0061] Step (3): The precursor was heated in an NH3 atmosphere (flow rate 100 mL min -1 ) and calcined at 700 °C for 3 h, then cooled; the heating rate was 5 °C min -1 ; Cooling rate: 3.3 ℃·min -1 ; Get Co 5.4 N;
[0062] Step (4): Prepare the positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was dispersed in 100 mL of anhydrous ethanol by ultrasonication, and then 2 wt% of Co 5.4 NMix well.
[0063] Step (5): evaporate the ethanol from the slurry obtained in step (4) in an oil bath at 80°C, and then dry it thoroughly in an oven at 120°C.
[0064] Step (6): The dried material obtained in step (5) is sintered in a muffle furnace at a sintering temperature of 400°C for 3 h to obtain a positive electrode material for a sodium ion battery.
[0065] Comparative Example 2:
[0066] Step (1): first, take 1 mmol of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water to obtain a ferric nitrate solution; then take 2 mmol of selenium powder and dissolve it in 5 mL of hydrazine hydrate to obtain a selenium-containing solution; add the selenium-containing solution dropwise to the ferric nitrate solution, and stir it magnetically for 15 minutes to obtain a mixed solution;
[0067] Step (2): The mixed solution obtained in step (1) was then transferred to a 100 mL hydrothermal reactor, maintained at 170 °C for 12 h, and then cooled to room temperature;
[0068] Step (3): The reaction product obtained in step (2) was centrifugally washed with deionized water and ethanol for three times each, dried at room temperature, and black powder FeSe2 was collected;
[0069] Step (4): Prepare the positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was ultrasonically dispersed in 100 mL of anhydrous ethanol, and then 2 wt% FeSe2 of the cathode material was added and mixed evenly;
[0070] Step (5): evaporate the ethanol from the slurry obtained in step (4) in an oil bath at 80°C, and then dry it thoroughly in an oven at 120°C;
[0071] Step (6): The dried material obtained in step (5) is sintered in a muffle furnace at a sintering temperature of 400°C for 3 h to obtain a positive electrode material for a sodium ion battery.
[0072] Comparative Example 3
[0073] The cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was ultrasonically dispersed in 100 mL of anhydrous ethanol, and then 2wt% CoN and 2wt% FeSe2 of the positive electrode material were added and mixed evenly. The mixed slurry was evaporated in an oil bath pot with an oil bath temperature of 80 °C and thoroughly dried in a 120 °C oven. The dried material was sintered in a muffle furnace at a sintering temperature of 400 °C and a sintering time of 3 h to obtain the positive electrode material for sodium ion batteries.
[0074] Comparative Example 4
[0075] The difference between Comparative Example 4 and Example 1 is that in step (7), Co 5.4 The added amounts of N and FeSe2 are 0.05wt% and 0.35wt% of the positive electrode material, respectively.
[0076] Comparative Example 5
[0077] The difference between Comparative Example 5 and Example 1 is that in step (7), Co 5.4 The added amounts of N and FeSe2 were 0.35wt% and 0.05wt% of the positive electrode material, respectively.
[0078] Embodiment 2:
[0079] Step (1): Mix 1 g Co(NO3)2·6H2O and 50 mL ethanol in a beaker equipped with a stirring bar and stir in air at room temperature for 24 h to form a homogeneous solution;
[0080] Step (2): evaporating the obtained homogeneous solution in an oil bath at 100° C. and vacuum drying overnight to obtain a precursor;
[0081] Step (3): The precursor was heated in an NH3 atmosphere (flow rate 100 mL min - 1 ) and calcined at 400 °C for 5 h, then cooled; the heating rate was 3 °C min -1 , cooling rate is 3 ℃·min -1 , prepare Co 5.4 N;
[0082] Step (4): first, take 1 mmol of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water to obtain a ferric nitrate solution; then take 3 mmol of selenium powder and dissolve it in 5 mL of hydrazine hydrate to obtain a selenium-rich solution; add the selenium-rich solution dropwise to the ferric nitrate solution, and stir it magnetically for 15 minutes to obtain a mixed solution;
[0083] Step (5): Transfer the mixed solution obtained in step (4) into a 100 mL hydrothermal reactor and maintain it at 220°C for 8 h. Cool it to room temperature;
[0084] Step (6): The reaction product obtained in step (5) was washed by centrifugation with deionized water and ethanol for three times respectively, dried at room temperature, and black powder FeSe2 was collected;
[0085] Step (7): Prepare the positive electrode material NaNi 0.5 Fe 0.3 Mn 0.2 O2 was ultrasonically dispersed in 100 mL of anhydrous ethanol, and then 1 wt% of Co as the positive electrode material was added. 5.4 N and 4wt% FeSe2 were mixed evenly;
[0086] Step (8): evaporate the ethanol from the slurry obtained in step (7) in an oil bath at 100°C, and then dry it thoroughly in an oven at 120°C;
[0087] Step (9): The dried material obtained in step (8) is sintered in a muffle furnace at a sintering temperature of 300° C. for 4 h to obtain a coated modified sodium ion battery positive electrode material.
[0088] Embodiment 3:
[0089] Step (1): Mix 1 g Co(NO3)2·6H2O and 50 mL ethanol in a beaker equipped with a stirring bar and stir in air at room temperature for 24 h to form a homogeneous solution;
[0090] Step (2): evaporating the obtained homogeneous solution in an oil bath at 100° C. and vacuum drying overnight to obtain a precursor;
[0091] Step (3): The precursor was heated in an NH3 atmosphere (flow rate 100 mL min - 1 ) and calcined at 1000 °C for 3 h, then cooled; the heating rate was 8 °C min -1 , cooling rate is 8 ℃·min -1 , prepare Co 5.4 N;
[0092] Step (4): first, take 1 mmol of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water to obtain a ferric nitrate solution; then take 1 mmol of selenium powder and dissolve it in 5 mL of hydrazine hydrate to obtain a selenium-rich solution; add the selenium-rich solution dropwise to the ferric nitrate solution, and stir magnetically for 15 min to obtain a mixed solution;
[0093] Step (5): The mixed solution was transferred to a 100 mL hydrothermal reactor, maintained at 120 °C for 15 h, and then cooled to room temperature;
[0094] Step (6): The reaction product obtained in step (5) was washed by centrifugation with deionized water and ethanol for three times each, dried at room temperature, and black powder FeSe2 was collected.
[0095] Step (7): Prepare the positive electrode material NaNi 0.2 Fe 0.4 Mn 0.4 O2 was ultrasonically dispersed in 100 mL of anhydrous ethanol, and then 4 wt% of Co as the positive electrode material was added. 5.4 N and 1wt% FeSe2 were mixed evenly;
[0096] Step (8): After the ethanol in the slurry obtained in step (7) is evaporated in an oil bath at 50°C, it is thoroughly dried in an oven at 120°C.
[0097] Step (9): The dried material obtained in step (8) is sintered in a muffle furnace at a sintering temperature of 450° C. for 2 h to obtain a coated modified sodium ion battery positive electrode material.
[0098] The positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-5 and the uncoated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、NaNi 0.5 Fe 0.3 Mn 0.2 O2、NaNi 0.2 Fe 0.4 Mn 0.4 O2 was weighed and ground according to the ratio of positive electrode material: conductive graphite: PVDF of 8:1:1, dissolved in an appropriate amount of N-methylpyrrolidone (NMP) and stirred evenly to form a slurry, and then the slurry was coated on the current collector aluminum foil, dried at 90 ° C in a blast dryer for 12 h, and punched into a disc electrode with a diameter of 12 mm. The disc electrode was used as the positive electrode, the metal sodium sheet was used as the negative electrode, 1 mol / L NaPF6 / EC+DEC+DMC (EC:DEC:DMC=1:1:1 volume ratio) was used as the electrolyte, and GF / D sodium ion battery separator was used. The button battery was assembled in the glove box according to the assembly order of the button battery.
[0099] The battery's electrical performance was tested in the following manner: operating voltage range 2.0-4.0 V, current density 1C, 50 cycles. The relationship between the number of cycles and the discharge specific capacity is as follows: Figure 3 and Figure 4 shown.
[0100] Comparative analysis of Example 1, Comparative Examples 1-5 and uncoated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Performance of batteries assembled with O2 positive electrode materials.
[0101] Example 1 obtained coated Co 5.4 The positive electrode material of N / FeSe2 makes the battery cycle performance the best, and the uncoated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The capacity of the battery assembled with O2 positive electrode material is the lowest; only Co 5.4 Although the battery assembled with positive electrode materials coated with Co or FeSe2 only showed slightly higher capacity and cycle stability, the overall performance improvement was not significant.5.4 The positive electrode materials of N and FeSe2 are different from those of Co-coated 5.4 Compared with a positive electrode material of N and FeSe2, the battery electrical performance is improved; however, if Co 5.4 When the coating ratio of N and FeSe2 exceeds a certain range, the electrochemical performance of the battery cannot reach the optimal level. When the coating process and coating amount are kept consistent, 5.4 N is replaced by CoN, the electrochemical performance of the battery is still inferior to that of the coated Co obtained in Example 1. 5.4 Batteries assembled with N / FeSe2 positive electrode materials.
[0102] and uncoated NaNi 0.5 Fe 0.3 Mn 0.2 O2、NaNi 0.2 Fe 0.4 Mn 0.4 Compared with the battery assembled with O2, the modified positive electrode materials coated in Example 2 and Example 3 significantly improve the cycle performance of the battery.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified sodium ion battery positive electrode material, characterized in that: The invention comprises a sodium ion battery positive electrode material matrix and a coating layer located on at least a part of the surface of the matrix, wherein the coating layer material is Co 5.4 N and FeSe2; The chemical formula of the sodium ion battery cathode material matrix is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4; In the coating layer material, Co 5.4 The mass ratio of N and FeSe2 is 1:4~4:1; The coating layer material accounts for 1-5% of the mass of the sodium ion battery positive electrode material matrix.
2. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: include: The sodium ion battery positive electrode material matrix, Co 5.4 N and FeSe2 are mixed in anhydrous ethanol, and heated and stirred until the solvent is evaporated to dryness to obtain a solid mixture; After the solid mixture is dried and sintered, a modified sodium ion battery positive electrode material is obtained.
3. The method for preparing the modified sodium ion battery positive electrode material according to claim 2, characterized in that: The sintering temperature is 300-450°C; the sintering time is 2-4 hours.
4. The method for preparing the modified sodium ion battery positive electrode material according to claim 2, characterized in that: The heating temperature of the heating and stirring is 50-120°C.
5. The method for preparing the modified sodium ion battery positive electrode material according to claim 2, characterized in that: The Co 5 .4 N is prepared by the following method: dissolving cobalt nitrate with crystal water in ethanol to form a solution, heating and stirring the solution to evaporate to obtain a solid, drying the solid to obtain a precursor, and calcining the precursor under an ammonia atmosphere to obtain Co 5 .4 N.
6. The method for preparing the modified sodium ion battery positive electrode material according to claim 5, characterized in that: The calcination temperature is 400-1000°C, and the calcination time is 1-5h; The heating rate during calcination is 3-8℃·min -1 The cooling rate after calcination is 3-8 ℃·min -1 .
7. The method for preparing the modified sodium ion battery positive electrode material according to claim 2, characterized in that: The FeSe2 is prepared by the following method: preparing ferric nitrate solution A, dissolving selenium powder in hydrazine hydrate to obtain solution B, adding solution B dropwise to solution A, stirring, and then performing a hydrothermal reaction, and the product is subjected to solid-liquid separation, washing and drying to obtain FeSe2.
8. The method for preparing the modified sodium ion battery positive electrode material according to claim 7, characterized in that: The temperature of the hydrothermal reaction is 120-220°C, and the time of the hydrothermal reaction is 8-15h; The molar ratio of the selenium powder to ferric nitrate is 1-3 mmol:1 mmol; the ratio of the selenium powder to hydrazine hydrate is 1-3 mmol:5 mL.
9. A sodium ion battery, characterized in that It includes the modified sodium ion battery positive electrode material as claimed in claim 1 or the modified sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 2 to 8.
